USE AND SATISFACTION OF LIBRARY RESOURCES AND SERVICES BY TEACHERS AND STUDENTS IN THE COLLEGES OF LUNGLEI DISTRICT: AN EVALUATIVE STUDY (LIS TODAY, 2023)
The present study has measured the use and satisfaction of library resources and services by  the teachers and students of four colleges of Lunglei districts of Mizoram. The colleges are  Lunglei Government College, Government J. Buana College, Government Hnahthial College,  and Higher and Technical Institute Mizoram (HATIM. The study is survey based with the help  of purposive sampling techniques. The total sample size is 240. The findings revealed that  majority of respondents are satisfied with textbook, reference collections, circulation and  reprographic service while nearly the whole respondent shows their Un-satisfaction with the  collection of e-resources and journal collection. Circulation and reprography services of the  library were more satisfactory to its users. Among the colleges, highest satisfaction was  observed in HATIM College.
Keywords: Library resources; library services; user satisfaction; Academic library